Dynamic Nuclear Polarization NMR Spectroscopy: Revealing Multiple Conformations in Lipid‐Anchored Peptide Vaccines1. Issue 41 (23rd August 2013) - Koers, Eline J.; López‐Deber, Maria Pilar; Weingarth, Markus; Nand, Deepak; Hickman, David T.; Mlaki Ndao, Dorin; Reis, Pedro; Granet, Anne; Pfeifer, Andrea; Muhs, Andreas; Baldus, Marc
<x xml:space="preserve">Abstract</x> Sensitivity is the key: Dynamic nuclear polarization NMR spectroscopy provides structural information on liposomal vaccines targeting Alzheimer's disease. DMPC/DMPG/Cholesterol mainly stabilizes extended structures of the lipid‐anchored peptide, while in DMTAP/Cholesterol liposomes the peptide adopts a multitude of conformations including random‐coil and extended structures.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>